Mental health condition of college students compared to non-students during COVID-19 lockdown: the CONFINS study - Julie Arsandaux; Marie Tournier; Christophe Tzourio; Ilaria Montagni; Shérazade Kinouani; Stéphane Schuck; Mélissa Macalli; Nathalie Texier; Mathilde Pouriel; Raphaël Germain; Adel Mebarki (BMJ Open)
Objectives To estimate the effect of student status on mental health condition during COVID-19 general lockdown in France.Design Cross-sectional analysis comparing students and non-students recruited in the same study.Setting Participants of the web-based CONFINS study implemented during the general lockdown in France in spring 2020.Participants 2260 participants (78% women) including 1335 students (59%).Primary and secondary outcome measures Through an online questionnaire, participants declared if they have experienced suicidal thoughts, coded their perceived stress on a 10-points scale and completed validated mental health scales (Patient Health Questionnaire-9 for depressive symptoms, Generalised Anxiety Disorder-7 for anxiety symptoms) during the last 7 days. The effect of college student status on each mental health condition was estimated using multivariate logistic regression analyses. Stratified models for students and non-students were performed to identify population-specific factors.Results Student status was associated with a higher frequency of depressive symptoms (adjusted OR (aOR)=1.58; 95% CI 1.17 to 2.14), anxiety symptoms (aOR=1.51; 95% CI 1.10 to 2.07), perceived stress (n=1919, aOR=1.70, 95% CI 1.26 to 2.29) and suicidal thoughts (n=1919, aOR=1.57, 95% CI 0.97 to 2.53). Lockdown conditions that could be potentially aggravating on mental health like isolation had a higher impact on students than on non-students.Conclusions College students were at higher risk of mental health disturbances during lockdown than non-students, even after taking into account several potential confounding factors. A close follow-up and monitoring of students’ mental health status is warranted during lockdown periods in this vulnerable population.